2016
DOI: 10.4081/monaldi.2008.388
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide rebreathing in non-invasive ventilation. Analysis of masks, expiratory ports and ventilatory modes

Abstract: In healthy volunteers, nasal and facial masks with EV prevent rebreathing. In addition, the use of spacers did not generate this undesirable phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Low EPAP translates into low flow rates during exhalation when most of the intentional ventilatory leak occurs; use of a face mask under these conditions may enhance CO 2 rebreathing. [12][13][14][15] Elevated levels of CO 2 accumulating during the night, particularly in patients who used the device the longest, could have led to overnight renal bicarbonate retention, with incomplete clearance during the daytime resulting in sustained metabolic alkalosis. Ordinarily, metabolic alkalosis should suppress ventilation so as to produce compensatory CO 2 retention that would minimize alkalemia.…”
Section: Intervention Methodology and Adaptive Servoventilation Issuesmentioning
confidence: 99%
“…Low EPAP translates into low flow rates during exhalation when most of the intentional ventilatory leak occurs; use of a face mask under these conditions may enhance CO 2 rebreathing. [12][13][14][15] Elevated levels of CO 2 accumulating during the night, particularly in patients who used the device the longest, could have led to overnight renal bicarbonate retention, with incomplete clearance during the daytime resulting in sustained metabolic alkalosis. Ordinarily, metabolic alkalosis should suppress ventilation so as to produce compensatory CO 2 retention that would minimize alkalemia.…”
Section: Intervention Methodology and Adaptive Servoventilation Issuesmentioning
confidence: 99%
“…Our reported findings with ONM are similar to what others have reported regarding clearing CO 2 from NIV masks while using a single limb circuit. Samolski et al [ 7 ] reported that a PEEP or EPAP level as low as 4 cm H 2 O effectively washed out CO 2 while using a single limb circuit to provide NIV [ 7 ]. To the best of our knowledge, this study is the first to report similar findings on mask interfaces while using a dual limb circuit and critical care ventilator.…”
Section: Discussionmentioning
confidence: 99%
“…Samolski et al [ 7 ] studied the CO 2 rebreathing while using a single limb circuit. They assessed the effect of the expiratory port location at different sites using nasal and oronasal masks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 rebreathing takes place mainly in single-limb circuits. Besides, the type of mask and expiratory port,23,33,34,3638 and the level of EPAP used,21,34 end-tidal CO 2 concentration (EtCO 2 ), RR, tidal volume (Vt), were also the factors influencing CO 2 rebreathing 35. However, the increasing level of EPAP was not as important as fixed-resistance exhalation devices since the leak flow rate of PEV was greater at ~4–5 cmH 2 O.…”
Section: Discussionmentioning
confidence: 99%